Explorations Around the Creative Process of Theatrical Acting - Vaccalluzzo, Victoria (2023)
In this paper, we review the compositional operations of acting in theater rehearsal based on the concept of equality scene (Rancière, 2012). We are interested in how the acting composition manifests itself in independent theater rehearsal read as a possible equality scene. The focus of this work is placed in the theatrical rehearsal and the acting composition. We will share possible theoretical approaches to the term theatrical rehearsal. We will carry out research on the categories and definitions that intervene in the acting repetition that occurs in the acting creative process during rehearsal. Whit the contributions around rehearsal in Alberto Ure (2003), the acting conception in instances of stage composition developed in Cancha con niebla (2003) by Ricardo Bartís, and the acting registers posed by Federico León (2005), we propose a theoretical panorama of the notion of rehearsal as a theatrical practice that frames the compositional tasks of acting. We will develop the proposal to review the notions of trial, loss, and recovery as acting operations that are presented in the compositional task of scenic creation processes. We understand that these three operations can be interpreted as keys for reading the rehearsal as a possible equality scene.